TRADISI MERANTAU MASYARAKAT MELAYU MENERUSI TEKS TERPILIH KARYA HAMKA: THE NOMADIC TRADITION OF THE MALAYS IN SELECTED HAMKA TEXTS - Ibrahim, Nurul Aina; Muhammad Apandi, Siti Nuranis (Jurnal Pengajian Melayu (JOMAS), 2021)
Abstract As recorded in selected texts written by Buya Hamka, the nomadic tradition of the Malays is loaded with culture and custom elements. The use of selected texts, namely ‘Merantau Ke Deli’ and ‘Di Bawah Lindungan Ka’bah’, was appropriate for the study. This paper also differs from other research due to applying a Western theory to a localised topic such as the Malays’ nomadic tradition. Overall, this study aimed to identify the nomadic tradition by the Malays through specific Hamka works and analysed factors that triggered that phenomenon by applying the theory of migration or the ‘Push and Pull’ Theory introduced by Everett S. Lee (1966). The researchers utilised a qualitative approach, strengthened by Lee’s theory. The theory suggests four factors – factors found within the place of origin, factors in the destination, obstacles and other personal factors. The study found that the Malay characters in Hamka’s works travelled to leave their origin due to poverty and gender issues. Factors at the destination were the promise of a more comfortable life and receiving higher education. It is hoped that this paper could be beneficial and used by researchers in future. Keywords: nomadic tradition, the Malay community, factors, concepts, Theory of Migration by Everett S. Lee.